Safety of vaginal erbium laser: A review of 113, 000 patients treated in the past 8 years. (19th October 2020) - Gambacciani, M.; Cervigni, M.; Gaspar, A.; Novakov Mikić, A.; Gaviria, J.; Koron, N.; Vizintin, Z.
Abstract: Background: Energy-based devices are becoming a popular option for minimally invasive vaginal procedures. The aim of this study was to obtain information on the frequency of occurrence of adverse effects (AEs) related to vaginal erbium laser (VEL™) treatment. Materials and methods: The global survey was conducted among practitioners using the non-ablative VEL™ (Fotona, Ljubljana, Slovenia). Users were invited to provide the number of patients treated with VEL™ and the number of observed laser-related AEs. Results: The survey was conducted from August 2018 to April 2019. Responses from 535 practitioners were collected, with a total of 113, 174 patients treated in the period from 2012 to 2019. Out of 535 respondents, 160 (30%) shared detailed information about the indications they treated in a population of 62, 727 patients, whereas 188 (35%) respondents provided information on the frequency of AEs observed in their treated population of 43, 095 patients. All observed AEs were mild to moderate, transient and appeared with low frequencies. Conclusions: Minimally invasive thermal-only laser treatment using the non-ablative VEL™ procedures appears to be safe and the incidence of AEs is low.